Impact of American investment in India - Saon Ray; Smita Miglani; Neha Malik (Indian Council for Research on International Economic Relations (ICRIER), 2015)
The United States is India's largest trade and investment partner and is engaged with India at various levels of economic cooperation. This paper studies the direct and indirect impact of US FDI inflows in India and identifies the challenges faced by US investors. The paper is based on secondary data and information from primary firm level surveys. Analysis of the secondary data helped in identifying sectors where the overall impact of US FDI was high. A primary survey was then conducted in selected sectors comprising in-depth personal interviews and consultation meetings with relevant stakeholders. The main contribution of this paper is to our understanding of the impact of FDI through these surveys. The largest recipient of US FDI in the last few years has been the services sector, followed by manufacturing. The sectors chosen for study in this paper are finance, fast-moving consumer goods (FMCG), IT, pharmaceuticals, consulting, and automobiles. They were chosen primarily because the spillovers (of the impact of investment) to the local/consumer level are relatively high. The primary survey of American firms and other stakeholders was carried out in Delhi NCR, Mumbai, Bengaluru and Hyderabad in 2013. The findings of the paper include some examples of the direct impact of American FDI - the employment generated by American firms in India is considerable. Exports from these firms are also significant.
Keywords: F21; F23; O25; O33; 330; Foreign direct investment; Multinational enterprises; Inward FDI; spillovers